2007
DOI: 10.1186/1465-9921-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact on respiratory tract infections of heptavalent pneumococcal conjugate vaccine administered at 3, 5 and 11 months of age

Abstract: Background: Medical and public health importance of pneumococcal infections justifies the implementation of measures capable of reducing their incidence and severity, and explains why the recently marketed heptavalent pneumococcal conjugate vaccine (PCV-7) has been widely studied by pediatricians. This study was designed to evaluate the impact of PCV-7 administered at 3, 5 and 11 months of age on respiratory tract infections in very young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…In some countries, the introduction of this vaccine was followed by declines not only in pneumonia cases, but also in AOM and bronchitis [35,36]. In contrast, an increase in invasive pneumonia was reported in Spain after the introduction of the vaccine [37].…”
Section: Discussionmentioning
confidence: 89%
“…In some countries, the introduction of this vaccine was followed by declines not only in pneumonia cases, but also in AOM and bronchitis [35,36]. In contrast, an increase in invasive pneumonia was reported in Spain after the introduction of the vaccine [37].…”
Section: Discussionmentioning
confidence: 89%
“…A population-based study in Israel demonstrated the effectiveness of PCVs was 40.7%, for the control of alveolar pneumonias [13]. However two Italian studies that evaluated the impact of 2 + 1 schedule found significant reductions for pneumonia endpoints [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…This effectiveness has been demonstrated both for a standard vaccination schedule of three doses in the first 6 months of life, followed by a toddler dose at 12 to 15 months of age (5,8,14,32,38,45), and for a simplified schedule with a two-dose primary series and a toddler dose at 11 to 12 months (9,10,12,19,41). Besides the direct benefits for vaccinated infants and children, the administration of PCV7 has a substantial indirect effect in reducing the incidence of pneumococcal disease in unvaccinated adults, especially in those 65 years of age and older (4,13,24).…”
mentioning
confidence: 99%